Exposing the Shadow of Technology and its Effects on Electoral Management in Nigeria: A Study of 2023 General Elections - Adebogun, Olayinka Babatunde; Falobi, Funmi; Eboseremen, Ehikioya Nathaniel; Onyejelem, Timothy Ekeledirichukwu (Budapest International Research and Critics University, 2025)
The 2023 general elections in Nigeria marked a watershed moment in the country’s democratic trajectory, particularly with the adoption of technology-driven electoral management systems such as the Bimodal Voter Accreditation System (BVAS) and the INEC Result Viewing Portal (IReV). While these innovations were introduced to enhance transparency, reduce electoral fraud, and strengthen public trust, their deployment exposed significant challenges that highlighted the shadow side of technology in electoral processes. This study interrogates the effects of technological tools on the credibility, efficiency, and legitimacy of the 2023 elections, drawing on media reports, official election data, and scholarly analyses. The study made use of secondary sources of Data collection. Secondary data were sourced from academic journals, INEC reports, election observer reports, news, articles, and policy papers. Databases such as ResearchGate, Google Scholar, and reputable news outlets were utilized. Findings reveal a paradox: although technology improved aspects of voter accreditation and broadened access to election results, systemic failures, infrastructural limitations, cyber vulnerabilities, and perceived manipulation undermined confidence in the process. The paper argues that the reliance on technology without adequate infrastructural support, legal clarity, and institutional integrity risks deepening public distrust rather than consolidating democratic gains. The study concludes that the 2023 Nigerian general election represents a pivotal case study in the intersection of technology and democracy in a developing nation. The introduction of advanced electoral technologies, such as the Bimodal Voter Accreditation System (BVAS) and the INEC Result Viewing Portal (IReV), was a bold step toward mdernzing Nigeria’s electoral process.